PENINGKATAN KETERAMPILAN MENULIS HANZI MENGGUNAKAN METODE DRILL DALAM PEMBELAJARAN BAHASA MANDARIN SISWA KELAS V SD ZION GKKA-UP MAKASSAR - Winda; Saud, Syukur; Azizah, Mir'ah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to improve the Hanzi writing skills of fifth-grade students at Zion GKKA-UP Elementary School, Makassar, through the implementation of the drill method. The participants consisted of 30 students. The study employed a Classroom Action Research (CAR) design conducted in two cycles. Qualitative data were collected through observation sheets of teacher and student activities, while quantitative data were obtained from the results of the Hanzi writing skill tests administered in Cycle I and Cycle II. The findings showed that the students' mean score on the Hanzi writing test increased from 65.0 (fair category) in Cycle I to 75.3 (good category) in Cycle II. This improvement was supported by the observation results, which indicated increased teacher and student participation throughout the learning process. The implementation of the drill method was therefore effective in improving the Hanzi writing skills of fifth-grade students in Mandarin language learning at Zion GKKA-UP Elementary School, Makassar.